2017
DOI: 10.3892/mmr.2017.7319
|View full text |Cite
|
Sign up to set email alerts
|

Interferon regulatory factor 4 (IRF4) is overexpressed in human non-small cell lung cancer (NSCLC) and activates the Notch signaling pathway

Abstract: The transcription factor, interferon regulatory factor 4 (IRF4), serves an essential role in the regulation of immune responses, and has been reported to act as a diagnostic and prognostic marker for various hematological malignancies. The present study aimed to investigate whether IRF4 could exert effects on human non-small cell lung cancer (NSCLC) and to explore the underlying mechanism. The mRNA and protein expression of IRF4 was detected in NSCLC tissues using reverse-transcription quantitative polymerase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 34 publications
2
21
1
Order By: Relevance
“…In contrast to A4GALT, CIB2, and PSMA1, high expression of IRF4 is associated with higher lung cancer patient survival. This appears to be inconsistent with published findings that IRF4 acts as an oncogene in NSCLC cell lines [30]. Like CIB2, IRF4 function in lung cancer remains to be clearly determined.…”
Section: Discussioncontrasting
confidence: 78%
“…In contrast to A4GALT, CIB2, and PSMA1, high expression of IRF4 is associated with higher lung cancer patient survival. This appears to be inconsistent with published findings that IRF4 acts as an oncogene in NSCLC cell lines [30]. Like CIB2, IRF4 function in lung cancer remains to be clearly determined.…”
Section: Discussioncontrasting
confidence: 78%
“…We observed that the combination of pomalidomide with the BET family antagonist JQ1 has additive effects in four of five pomalidomide-insensitive cell lines. Further analyses, as well as in vivo studies, are needed to confirm the efficacy of IMiDs and BET-bromodomain inhibitors combination therapy in ALCL and other tumors with de-regulated IRF4 [ 67 ]. Importantly, our data confirm the study by Weilemann et al, that demonstrated a key role of IRF4 in ALCL, irrespective of ALK status [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The two largest genetic-association studies of SCC (18) and BCC (22) identified multiple risk loci near pigmentation genes (for SCC SLC45A2, IRF4, TYR, HERC2, DEF8, and RALY; for BCC MC1R, IRF4, TYRP1, HERC2, LPP, and BNC2), supporting the well-established role of lighter pigmentation, and its interaction with UV radiation exposure, in the risk of KC. The association of genetic variants in regions of FOXP1 and IRF4 also implicate Notch signaling (30)(31)(32) in both SCC and BCC susceptibility. Patients with Bloom, Werner, and Rothmund-Thomson syndromes are at increased risk of BCC and SCC, implicating chromosomal instability as another shared KC risk factor (14,15).…”
Section: Biological Pathways Involved In Kc Developmentmentioning
confidence: 98%